EFEKTIFITAS PENAMBAHAN ASAM AMINO PADA PAKAN UNTUK PERTUMBUHAN IKAN SIDAT, Anguilla bicolor (McCelland, 1844) - Pratama, Ricky Hadi; Tarsim, Tarsim; Yudha, Indra Gumay (University of Lampung, 2019)
Eel is one of the fisheries commodity that have not been rearing widelyin Indonesia. Constraint that occured in rearing eel is slow growth. A way to accelerate eel growth isfeeding with enrichment by using an amino acids. An amino acids can be used directly by eel for cell growth and the formation of body tissue. An amino acid that is used from the stingrays are not utilized by peopleÂ because it has no economic value to production activities. This research was aimed to study the growth rate of eel whichis fed with enrichment of an amino acids derived from stingray extract. The method in this research used completely randomized design (CRD) with 3 treatments and 3 replications. The measure of eel that usedare 26-28 cm, the average weight is 28 grams and an amino acids dosage that used are 0 ml, 0.5 ml and 1 ml. It use FR 3% which is given at night to support the characteristic of eel that is nocturnal (active at night). The analyze result from the parameters that have been observed, there is not a significant effect (P> 0.05) and the fed with enrichment by using an amino acids with the dosage used hasn't been able to be utilized as fish feed mixture to increase growth rate.